STRATEGI PARTAI KEADILAN SEJAHTERA KABUPATEN ROKAN HILIR DALAM MENINGKATKAN JUMLAH KURSI PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2019 - Hidayat, Salman; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the political strategy of the Prosperous Justice Party (PKS) in its efforts to increase its seat count in the Rokan Hilir Regency Regional Representative Council (DPRD) in the 2019 Legislative Election. The study focuses on the party's offensive and defensive strategies, as well as the supporting and inhibiting factors influencing their success. The research method used was a qualitative approach, with data collection techniques through interviews and documentation.The results indicate that PKS implemented an offensive strategy through expanding its voter base, penetrating relevant local issues, recruiting potential legislative candidates, and employing creative digital and volunteer-based campaigns. Meanwhile, its defensive strategy involved consolidating its loyalist base, strengthening its cadre network, and maintaining emotional connections with regular voters through social and religious programs. The success of this strategy is reflected in the significant increase in PKS's seat count, from one seat in the 2014 election to four seats in the 2019 election (KPU data, 2019).Despite this, PKS also faced several obstacles, such as limited campaign funds and the strong dominance of major parties like PDI-P, Golkar, and Nasdem, which already had established political bases in Rokan Hilir. However, through an intensive and consistent grassroots approach, PKS succeeded in penetrating some strategic voter bases, particularly among religious communities and youth.This study concludes that PKS's success in increasing its electability and political representation in Rokan Hilir was the result of a comprehensive strategy, adaptive to local dynamics, and supported by the militancy of party cadres and volunteers. These findings are expected to serve as a reference for other political parties in formulating winning strategies in this competitive region Keyword: Political strategy, Prosperous Justice Party, 2019 Election, Rokan Hilir, base consolidation, political campaign.